Differential expression profiles and bioinformatics analysis of microRNAs in brown adipose tissue dysfunction induced by chronic intermittent hypoxia in obstructive sleep apnea - Ji, Meilin; Guo, Yaopeng; Zhang, Jinjie; Lin, Shu; Li, Liangyi; Chen, Qingshi (Frontiers in Cell and Developmental Biology, 2025)
Obstructive sleep apnea (OSA) is a sleep-related respiratory disorder. Although recent studies have shown that OSA may be an alterable risk factor for metabolic syndrome (MS), the precise mechanism remains unknown. This study was designed with the purpose of identifying differentially expressed microRNAs (DEmiRs) in OSA-induced brown adipose tissue (BAT) injury. In this study, mouse models of chronic intermittent hypoxia (CIH)-related BAT injury were established using APOE mice. The microRNAs (miRNAs) expression profiles of the CIH-caused BAT injury were analyzed by the miRNA sequencing technology. The miRNA-seq data were analyzed using Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. An analysis of real-time quantitative PCR (RT-qPCR) confirmed the presence of several typical miRNAs. Ultimately, we constructed a network to illustrate the correlation between the miRNAs and target genes. In the CIH-induced BAT damage mouse models, 7 miRNAs experienced an upregulation, and 16 miRNAs underwent a downregulation. Six DEmiRs were confirmed using RT-qPCR. Additionally, GO and KEGG analyses were adopted to annotate the potential biological role of miRNAs. As a final step, we construct a miRNA–mRNA network for predicting miRNAs target genes. In conclusion, we first discovered that OSA-induced BAT dysfunction is associated with abnormal miRNA expression. This study exhibited a novel understanding of the potential molecular mechanism of OSA-related MS.